Compliance Level of Textual Therapeutic Usage of Kshirakakoli Containing Formulations with a Serial Ethnomedicinal Survey and Modern System of Medicine - Gunpreet Kaur; Vikas Gupta; Ravinder Sharma; Sanjiv Kumar; R G Singhal; Ranjit Singh; Parveen Bansal (Biology, Medicine, & Natural Product Chemistry, 2021)
Fritillaria roylei (Kshirakakoli) is a primal plant used in ancient times. But nowadays, due to biotic and abiotic stress the plant has entered in the list of threatened medicinal plant. In ancient texts effective uses of formulations containing kshirakakoli are well mentioned but the information is not written in simple language due to which the therapeutic value of the plant is not well understood by scientific fraternity. So, there is a major need to perform ethno medicinal survey for the formulations containing kshirakakoli and compare their therapeutic uses as mentioned in text with the modern system of medicine. In this study, a field survey was performed in 4 states i.e., Uttar Pradesh, Uttrakhand, Punjab and Himachal Pradesh where the conversation regarding usage of this plant or formulation was done with 24 local medical practitioners, 18 shopkeepers and 4 traditional healers. The information thus obtained were recorded and then compared. Results showed that the usage of kshirakakoli containing formulations was highest in Himachal Pradesh and Uttrakhand. Only few clinical studies have been done on these formulations. The effectiveness of the formulations against remedies alluded by the trado-medical practitioners claimed was found accurate as per ayurvedic textual literature. Hence, the ethno medicinal survey provides a precise guidance to scientists for future research on these kshirakakoli containing formulations that are useful in plethora of disorders.